2014
DOI: 10.3389/fnsys.2014.00009
|View full text |Cite
|
Sign up to set email alerts
|

Marked reduction of cerebellar deficits in upper limbs following transcranial cerebello-cerebral DC stimulation: tremor reduction and re-programming of the timing of antagonist commands

Abstract: Cerebellar ataxias represent a very heterogeneous group of disabling disorders for which we lack effective symptomatic therapies in most cases. There is currently an intense interest in the use of non-invasive transcranial DC stimulation (tDCS) to modulate the activity of the cerebellum in ataxic disorders. We performed a detailed laboratory assessment of the effects of transcranial cerebello-cerebral DC stimulation (tCCDCS, including a sham procedure) on upper limb tremor and dysmetria in 2 patients presentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 48 publications
0
57
0
Order By: Relevance
“…Non-invasive stimulation of the cerebellum can modify the connectivity between the cerebellum and primary motor cortex (M1), by putative polarisation of Purkinje cells in the cerebellar cortex [5,6]. Small clinical studies have indicated that non-invasive cerebellar stimulation has potential as a novel treatment intervention in neurological conditions exhibiting cerebellar pathology [7][8][9][10][11][12]. However, the mechanisms of action are incompletely understood [6,10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive stimulation of the cerebellum can modify the connectivity between the cerebellum and primary motor cortex (M1), by putative polarisation of Purkinje cells in the cerebellar cortex [5,6]. Small clinical studies have indicated that non-invasive cerebellar stimulation has potential as a novel treatment intervention in neurological conditions exhibiting cerebellar pathology [7][8][9][10][11][12]. However, the mechanisms of action are incompletely understood [6,10,13].…”
Section: Introductionmentioning
confidence: 99%
“…), or contralateral supra‐orbital area (Grimaldi & Manto, ; Grimaldi et al . ), or the motor cortex (Macher et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…In a further study, the same authors (Grimaldi et al . ) assessed the effects of a novel protocol using transcranial DC stimulation applied in the same session to the motor cortex (cathodal) and cerebellum (anodal) (cerebello‐cerebral DC stimulation) on tremor, EMG activity and dysmetria in two patients with spinocerebellar ataxia type 2. The rationale for using this paired cerebro‐cerebellar stimulation arises from the observation that cathodal motor cortical DC stimulation improves some features related to a cerebellar deficit (Pozzi et al .…”
Section: Introductionmentioning
confidence: 99%
“…In another report, tDCS over the cerebellum and contralateral motor cortex reduced postural and action tremor due to the degenerative cerebellum in patients [140]. rTMS over the cerebellum in patients with cerebellar stroke and cerebellar ataxia improves ICARS subscore on gait and posture with improvement in neurophysiological parameters, such as CBI [61].…”
Section: Noninvasive Brain Stimulation (Nibs)mentioning
confidence: 91%
“…Furthermore, the NIBS to the cerebellum modulates cerebellar excitability [98,[129][130][131], motor function [132,133], and motor learning [32,[134][135][136][137][138] in healthy population. In patients with cerebellar ataxia, some previous studies reported about the effect of tDCS to the cerebellum on motor function [131,[139][140][141]. A double-blind, randomized and sham-controlled study revealed that cerebellar tDCS improved SARA, ICARS, nine-hole peg test, and gait speed [141].…”
Section: Noninvasive Brain Stimulation (Nibs)mentioning
confidence: 99%